Prevalence of Upper Trapezius Tightness Due to Chronic Neck Pain and Poor Posture in University going Students - Momina Najeeb, Sumbal Habib, Noor Mahmood, Maryam Kamal, Mubashr Awajid, Hijab Aslam, Imran Hussain, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: This study aimed to find out the prevalence of upper trapezius tightness due to chronic neck pain and poor posture in university students. Methods: An observational study design was opted for this research and a sample size of 360 participants were enrolled using non probability convenient sampling technique. Participants were selected on the basis of inclusion criteria which was undergraduate students of both gender above age 18 years. Data was collected using upper trapezius muscle length test to assess muscle tightness and Neck Pain Index Disability (NDI) questionnaire. For statistical analysis, SPSS version.24 was used and prevalence was interpreted using frequency tables and graphs. Association with chronic neck pain and poor posture was determined using chi square. P<0.05 was considered to be significant. Results: Upper trapezius tightness was found quite prevalent among university students. Results showed that 53.9% students could not lift heavy objects. 68.1% students could not read properly, 74.2% students had headache, 60% of students could not concentrate properly, 60.3% students had issues regarding sleep and 51.4% students could not be able to perform their recreational activities because of chronic pain in neck and poor postures while 52% students can drive easily with normal pain intensity due to upper trapezius tightness. Practical implication: This observational study would add and authenticate an evidence to the literature among the certain study population. This study would educate the university students and general population about posture related muscle pain and tightness which would help them identify the association between posture and muscular imbalance. Conclusion: This study concluded that upper trapezius tightness is highly prevalent among university student and it is strongly associated with chronic neck pain and poor posture. Keywords: Trapezius Muscle, Muscle Tightness, Neck Pain, Poor Posture, University Student.